A new species of Polypedates Tschudi, 1838 (Amphibia: Anura: Rhacophoridae) from West Bengal State, Eastern India - Purkayastha, Jayaditya; Das, Madhurima; Mondal, Kingshuk; Mitra, Shibajee; Chaudhuri, Anirban; Das, Indraneil (Zootaxa, 2019)
A new species of frog belonging to the genus Polypedates Tschudi is described from the state of West Bengal, Eastern India. A mid-sized frog, SVL ranges from 47.9–53.6 mm in males and 72.0 mm in the single female. The species is diagnosable in showing the following suite of characters: digits lack webbing, inner and outer metacarpal tubercles present; no dermal fold on forearm; toes webbed, webbing formula I1–1 II0.5–2III1–2IV2–0.5V; an inner metatarsal tubercle present; tibio-tarsal articulation reaches between eye and nostril; and skin on forehead co-ossified to cranium. Additionally, males possess paired vocal sacs. The new species is compared with known species of the genus Polypedates.